Mechanism of modified mRNA structure in COVID-19 vaccines for inducing neutralizing antibodies - Sabighoh Zanjabila; Beti Ernawati Dewi (Indonesian Society for Biochemistry and Molecular Biology, 2024)
The development of SARS-CoV-2 mRNA vaccines is closely linked to advancements in mRNA manufacturing technology. Structural modifications, such as replacing uridine with 1-methylpseudouridine (1mψ), enhance translation efficiency and help the mRNA evade immune detection. Lipid nanoparticles (LNPs) serve as an effective delivery system. Vaccines like BNT162b2 and mRNA-1273 target the receptor-binding domain (RBD) of the spike (S) protein, prompting B cells to produce neutralizing antibodies that block the RBD from binding to the Angiotensin-Converting Enzyme 2 (ACE2) receptor, preventing infection. These vaccines also stimulate adaptive immune responses by activating CD4+ and CD8+ T cells, with mRNA functioning as an endogenous antigen. Antigen-presenting cells (APCs) present the vaccine antigens via major histocompatibility complex (MHC) class I and II pathways, with CD8+ T cells recognizing MHC class I and destroying infected cells, while CD4+ T cells recognize MHC class II and assist in B cell maturation and antibody production. While mRNA vaccines have proven effective in neutralizing SARS-CoV-2, challenges remain, including the decline in neutralizing antibody titers over time and the emergence of new viral variants.